TEACHING OF MEDICAL MICROBIOLOGY - COMMENTS ON BASIC VERSUS APPLIED ASPECTS RELATED TO PROFESSION - Montelli, A. C. (Soc Brasileira Microbiologia, 1993)
Comments about education and medicine teaching were made. The learning and the curriculum in according with the priorities of the country's health had special emphasis.Students and teachers of Botucatu considered that the improvement of the 2nd year medical microbiological course was good with predominantly basic contents. The students prefer a balanced content or predominantly applied to medicine.Three phases of the teaching of microbiological contents are proposed: 1st - in the basic cycly (2nd year); 2nd - into the course of Clinical Laboratory (3rd or 4th year); 3rd - into the clinical cycle, following a program of integration.
Keywords: MEDICAL MICROBIOLOGY; TEACHING; OBJECTIVES